Simultaneous Determination of Electron and Hole Mobilities in InP/InGaAsP/InAs/InP Laser Heterostructure by Admittance Spectroscopy - Kuruoglu, Neslihan Ayarci; Ozdemir, Orhan; Bozkurt, Kutsal; Belahsene, Sofiane; Martinez, Anthony; Ramdane, Abderrahim (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2017)
Temperature- and field-dependent electron and hole mobilities were simultaneously derived from admittance measurements on an InP/InGaAsP/InAs/InP long wavelength laser structure. Each carrier's mobility was separated in the frequency domain due to the corresponding different relaxation times from C versus log f curves. Derived electron and hole mobilities followed the Poole-Frenkel-type field dependence, indicating the transport of carriers through hopping. Extracted thermal energy gap (Delta) and disorder temperature (T-0) values were in mutual agreement with previous current density-voltage measurements and from the energy band diagram of the present structure, constructed from other studies in the literature by photoluminescence and photoluminescence excitation experiments.
Keywords: Capacitance-voltage characteristics; charge carrier mobility; p-i-n diodes; VERTICAL CARRIER TRANSPORT; QUANTUM-DOT LASERS; MU-M; THRESHOLD CURRENT; TEMPERATURE; FIELD; Engineering; Physics